Peningkatan Kemampuan Menulis Esai Narasi Melalui Teknik Mind Mapping Pada Mata Pelajaran Bahasa Indonesia Di Era Merdeka Belajar Kelas V UPTD SD Negeri 53 Parepare - Hadijah, Hadijah; Hamsiah, Andi; Asdar, Asdar (Jounal of Primary Education, 2023)
Penelitian bertujuan untuk mengetahui peningkatan aktivitas belajar siswa melalui penerapan teknik mind mapping dan untuk mendeskripsikan peningkatan kemampuan menulis Esai Narasi melalui penerapan teknik mind mapping pada siswa kelas V UPTD SD Negeri 53 Parepare. Penelitian ini menggunakan pendekatan kualitatif, metode deskriptif, bentuk penelitian tindakan kelas (PTK), . Hasil penilaian kemampuan menulis esai narasi dari base line sampai siklus II dengan skor rata-rata yaitu (61,1), (69), (81,18). Hasil penilaian Ketuntasan Belajar sampai siklus II yaitu siklus I (tuntas 43%, dan tidak tuntas 57%) dan untuk siklus II (tuntas 90% dan tidak tuntas 10%) Kesimpulan, proses pelaksanaan pembelajaran dan kemampuan menulis esai narasi melalu teknik mind mapping pada siswa kelas V mengalami peningkatan. The purpose of this study to know the increase in student learning activities through the application of mind mapping techniques and to describe the improvement of the ability to write narrative essays through the application of mind mapping techniques at class V UPTD students SD Negeri 53 Parepare. This study used a qualitative approach with descriptive methods. The form of research is Classroom Action Research (PTK). The assessment results show that the ability to write narrative essays from the base line to cycle II with an average score of (61.1), (69), (81.18). The results of the Learning Completeness assessment until cycle II are cycle I (43% complete, and 57% incomplete) and for cycle II (90% complete and 10% incomplete). Based on the data obtained, it can be concluded that the learning implementation process and the ability to write narrative essays through the mind mapping technique have increased at class V UPTD students SD Negeri 53 Parepare.